"SIMPLE AS DO RE ME, ABC": LANGUAGE, MUSIC, AND WORKING MEMORY - Atherton, Ryan P. (My University, 2013)
The present study examines the underlying cognitive framework involved in the active processing of information. Active processing takes place in working memory, popularly associated with Baddeley and Hitch's (1974) multicomponent working memory model. According to this model, incoming information from the environment is temporarily stored to perform verbal and nonverbal tasks. Information is stored in one of two formats: visuospatial or phonological. Important to the present experiment is phonological information. Phonological information refers to the sounds of language (e.g., speech), that occur in a phonological store and are maintained there by rehearsal via an articulatory loop. Yet, the storage of phonological information in the multicomponent working memory model does not account for all auditory information (e.g., music). Research investigating this discrepancy has produced inconclusive findings. Whether or not phonological and non-linguistic auditory information share a structure for storage in working memory is still unknown. The current study benefits from the utilization of an auditory interference task to help rectify this inconsistency. Results indicate that linguistic and musical information do not completely share a storage mechanism in the multicomponent working memory model, however, they are not completely separate either. Also, musicians and non-musicians may exhibit different cognitive underpinnings in the storage of linguistic and musical information.
Partial Fulfillment of the Requirements For the Degree of Master of Science-Psychology - Cognitive and Affective Science
Keywords: Effect of music on cognition; Attention; Music; Performance; Working memory; Phonological loop; Language